2010
DOI: 10.1136/thx.2009.125856
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Nrf2 and gluthathione-S-transferase polymorphisms do not modify associations of prenatal tobacco smoke exposure with asthma and lung function in school-aged children

Abstract: Background Maternal smoking during pregnancy has detrimental effects on the respiratory health of infants and children. Polymorphisms of antioxidant genes including glutathione-S-transferases (GSTs) have been proposed as candidates for asthma and reduced lung function in children. Methods Women enrolled in the Avon Longitudinal Study of Parents and Children reported smoking habits during pregnancy. Asthma status in their children was established at age 7.5 years from parental reports and lung function was meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 46 publications
1
20
0
1
Order By: Relevance
“…Our findings on the effect of SHS exposure on lung function are consistent with the results of studies conducted in other countries and areas [9,[21][22][23][24][25][26][27][28][29] , which also provided evidence of an association between SHS exposure and respiratory outcomes. For example, a study in the US, conducted by the National Health and Nutrition Examination Survey, on children 4-16 years of age identified an association between current SHS and reduced lung function, although there was a different effect for different age groups [24] .…”
Section: Discussionsupporting
confidence: 82%
“…Our findings on the effect of SHS exposure on lung function are consistent with the results of studies conducted in other countries and areas [9,[21][22][23][24][25][26][27][28][29] , which also provided evidence of an association between SHS exposure and respiratory outcomes. For example, a study in the US, conducted by the National Health and Nutrition Examination Survey, on children 4-16 years of age identified an association between current SHS and reduced lung function, although there was a different effect for different age groups [24] .…”
Section: Discussionsupporting
confidence: 82%
“…Two subsequent independent epidemiological studies have demonstrated that in utero exposure to folate (a methylating agent) is associated with the risk of developing asthma in humans (51,52). In utero exposure to cigarette smoke is also associated with the development of asthma in children (55,56), and given the recent evidence for modulation of epigenetic marks by cigarette smoke, it is possible that changes in DNA methylation or specific histone modifications mediate the effect of prenatal exposure to cigarette smoke on the development of allergic airway disease; no publications to date have demonstrated this link.…”
Section: Epigenetics and Lung Diseasementioning
confidence: 99%
“…One study contained four case-control studies from different ethnicities (Gilliland et al, 2002), and two studies contained two individual case-control studies, respectively (Kamada et al, 2007;Minelli et al, 2010). Finally, 19 casecontrol studies from 14 publications with 4,543 childhood asthma cases and 19,394 controls were included into this meta-analysis (Vavilin et al, 2000;Gilliland et al, 2002;Kabesch et al, 2004;Lee et al, 2005;Ercan et al, 2006;Hanene et al, 2007;Kamada et al, 2007;Li et al, 2009;Henderson et al, 2010;Lima et al, 2010;Minelli et al, 2010;Tung et al, 2011;Karam et al, 2012;Piacentini et al, 2012). Among those 19 case-control studies, 8 (75.0%) were from Caucasian populations, and 6 (12.5%) were from Asians and 3 from Africans (Table 1).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%